Air composition and chemistry - Peter Brimblecombe (New York Cambridge University Press, 1996)
This book is about the atmosphere and mankind's influence on it. Although air chemistry is probably one of the oldest branches of chemistry, it is now the focus of considerable public interest. The second edition of this extremely popular text has been rewritten and all information updated, to keep pace with this important and fast moving science.
Keywords: Atmospheric currents, winds